2022
DOI: 10.3390/ijerph191610196
|View full text |Cite
|
Sign up to set email alerts
|

Career Capital and Well-Being: A Configurational Perspective

Abstract: This study explored the configuration effect of human capital, social capital, and psychological capital on employee well-being. A total of 458 employees were investigated via a human capital scale, social capital scale, Chinese psychological capital scale, and multiple well-being questionnaire. The result of the fuzzy-set qualitative comparative analysis showed that human capital, social capital, and psychological capital in the form of diversified configuration will achieve high well-being, characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…We found a significant total effect of teachers’ psychological capital on workplace well-being, which supported the findings of previous studies [ 21 , 22 , 23 ]. Luthans’s psychological capital theory proposes that psychological capital consists of four positive factors (self-efficacy, optimism, hope, and resilience), which are critical aspects of employee and organizational success [ 60 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We found a significant total effect of teachers’ psychological capital on workplace well-being, which supported the findings of previous studies [ 21 , 22 , 23 ]. Luthans’s psychological capital theory proposes that psychological capital consists of four positive factors (self-efficacy, optimism, hope, and resilience), which are critical aspects of employee and organizational success [ 60 ].…”
Section: Discussionsupporting
confidence: 92%
“…Some empirical research has shown that psychological capital can predict workplace well-being [ 21 , 22 , 23 ]. Psychological capital is a general term for various positive mental states including self-efficacy (confidence), hope, optimism, tenacity, emotional intelligence and so on, which play a catalytic role in the process of personal growth and performance improvement [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous scholars have also examined similar studies (Xu, Hou, Zhang, Yu, Guan, et al, 2022; Xu, Hou, Zhang, Yu, & Li, 2022; Xu et al 2023). Xu, Hou, Zhang, Yu, Guan, et al (2022), Xu, Hou, Zhang, Yu, and Li (2022), Xu et al (2023) used configuration perspective to examine the effects of human capital, social capital, and PsyCap on well-being, job performance, and career adaptability.…”
Section: Theoretical Backgroundmentioning
confidence: 99%